SUSTAINABLE PUBLIC BIDDINGS: THE CASE OF UNIVERSIDADE FEDERAL DA FRONTEIRA SUL’S UNIVERSITY RESTAURANT - Weber, Josiane; Machado, Nelson Santos (RACE - Revista de Administração, Contabilidade e Economia, 2016)
This study attempted to verify how the Universidade Federal da Fronteira Sul (UFFS) contemplated the three pillars of sustainability on the bidding processes to the implantation of its university restaurants. A qualitative research through a case study was performed. The methods of data collection were literature, documentary research to analyze 11 cases occurred between 2010 and 2014, and interviews, in order to identify the responsible for the area’s perception concerning the sustainable procurements. Data analysis revealed that, in general, the involved people have a wide perception on the subject, covering the three pillars of sustainability. The Institution seeks to include sustainability criteria in their bidding processes, however, it is observed noticeable emphasis on economic and environmental criteria, confirming what has been shown in theory and studies related. Considering these aspects, it is concluded that, in order to meet the three pillars of sustainability, the institution must also pay attention to the social issues, even though to do so it needs to include additional criteria to the ones proposed by legislation. Among the proposals of improvements, two of them stand out: investing in academic community’s awareness and creating a Sustainability Center of institutional nature to reflect and plan the advances, in particular, in Social Pillar. Keywords: Sustainability. Sustainable public biddings. Triple Bottom Line.